Tax Justice: A Study of Value Added Tax (VAT) Policy in Indonesia - Taqwallah Taqwallah; Sigit Nurhadi Nugraha (Journal of Public Representative and Society Provision, 2026)
Taxes are a vital instrument in supporting national development, with Value Added Tax (VAT) becoming a primary source of state revenue since its enactment through Law No. 8 of 1983. The most recent reform, Law No. 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP), raised the VAT rate from 10% to 11% as of April 2022, with a planned 12% increase by 2025. This research uses a qualitative, descriptive approach by analyzing laws and regulations, secondary data from the Ministry of Finance and Statistics Indonesia (BPS), and academic studies, complemented by normative and empirical analyses. The results show that the VAT rate increase contributed significantly to increased state revenue, strengthened the post-pandemic fiscal situation, and maintained stable economic growth of around 5%. However, this policy impacted public purchasing power, particularly among the lower-middle class, who are sensitive to price increases, resulting in decreased consumption of non-essential goods. MSMEs were also impacted through decreased demand and increased production costs. Although the government provides VAT exemptions for basic necessities such as staple foods, education, and health care, as well as incentives for MSMEs, the regressive nature of VAT still creates the potential for injustice. Legally, this policy is valid under Article 23A of the 1945 Constitution, but public legitimacy is largely determined by perceptions of fairness. Therefore, while successful in increasing state revenue, the VAT policy must be balanced with social protection, subsidies, and strengthening the principle of tax fairness so that its benefits are felt equally by all levels of society.